Mass Production and Application of Spodoptera pectinicornis as Biological Control Agent of Water lettuce (Pistia stratiotes) - Helda Orbani Rosa; Samharinto .; Lyswiana Aphrodyanti (Center for Journal Management and Publication, 2017)
Water lettuce (Pistia stratiotes) is one of the important aquatic weeds because it can cause many problems for humans and the environment. In addition, the declining quality and quantity of water is also due to the invasion of water lettuce weeds covering the surface of waters, which can lead to the increasing transpiration and destruction of plankton making the balance of the ecosystem disrupted. This study was conducted in an attempt to control P. Stratiotes by utilizing the biological control agent Spodoptera pectinicornis with mass production and its releasing applications in South Kalimantan’s waters. The study was started by taking and collecting S. pectinicornis from several places/fields. The moths were then placed in trays of water and put in a gauze cage of 75 cm x 75 cm x 75 cm in order to keep the air circulation. They were nourished in the laboratory to produce groups of eggs. The groups of eggs were then transferred to rearing ponds. When a fair number of agents were obtained, the treatment of liquid fertilizer AB Mix was carried out. The results showed that the fertilization treatment to water lettuce weeds as the food for the biological control agent S. pectinicornis did not differ from the condition when there was no fertilization treatment either on the feeding ability, weight of larvae and pupae or fitness of imago. However, its destructive ability is high that it has a big potential as a biological control of water lettuce.